Lao PDR : Building an Economy That Works Again - World Bank (World Bank, Washington, DC, 2021)
Lao PDR is currently facing the phenomenon of jobless growth. This trend started in the early 2010s when non-farm job creation stagnated despite rapid growth in gross domestic product (GDP). The labor market suffered from weak activity in the private sector, with all sectors apart from hospitality losing jobs. Jobless growth has prevented the Lao PDR economy from reaping its demographic dividend. Reversing the decline in job creation is essential for fostering inclusive growth in Lao PDR. Promoting inclusive growth requires both facilitating higher participation in the workforce along with continued investments in skills, as well as a greater creation of productive and rewarding jobs. This note explores the factors associated with jobless growth in Lao PDR: deteriorating private sector conditions as well as skills and spatial mismatch in employment. The structure of the note is as follows. Section 2 discusses the impact of the deterioration in private sector conditions on job creation and the constraints that have caused firms to downsize or exit the market; Section 3 explores the impact of job loss on workers of different skill levels, and in causing skills mismatch in the labor market; Section 4 examines the geography of jobs and the spatial dimension of employment; and Section 5 concludes with policy recommendations, proposing measures to revive the private sector and restart the engine of job creation, as well as to reduce inter-regional disparities by better matching jobs to workers.